Supramolecular Gels With Controllable Degradation for Suppressing Tumor Recurrence and Relieving Postoperative Pain - Jiangtao Lin; Bin Liu; Quan Wang; Yi Duan; Yijie Qiu; Qi Wu; Qi Wang; Yi Dong; Hao Fu; Xinyue Wang; Yourong Duan (Aggregate)
ABSTRACT Postoperative pain and tumor recurrence are critical challenges following malignant tumor resection. To address these issues, we developed a supramolecular gel delivery system loaded with ropivacaine microcrystals (RopC Gel). Using PEG400 as the solvent, we successfully screened and identified matrix materials capable of forming supramolecular hydrogels through a heating–cooling process. By strategically leveraging the hydrophilic and hydrophobic properties of the gel matrix, we controlled its mechanical strength and degradation rate by adjusting the ratio of hydrophilic to hydrophobic components, resulting in a degradable, injectable, and self‐healing gel delivery system. In both rat plantar incision and mouse tumor resection pain models, RopC Gel provided long‐lasting analgesia for up to 5 days. Notably, tumor‐resected mice treated with RopC Gel demonstrated extended survival and slower tumor progression. Further in vitro and in vivo experiments revealed that RopC Gel affects mitochondrial function by promoting the accumulation of reactive oxygen species in tumor cells, inducing pyroptosis, stimulating immunogenic cell death (ICD), and activating anti‐tumor immune responses. This work offers an innovative solution for postoperative tumor resection management. Additionally, the controllable degradation properties outlined in this study provide an efficient strategy for the controlled release of multiple drugs, with the potential for widespread clinical applications.